2016
DOI: 10.1039/c6cc02290a
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell-targeted two-photon fluorescence probe for the real-time ratiometric imaging of DNA damage

Abstract: Real-time imaging of DNA damage in cancer cells could provide valuable information on the formation and development of cancer. Herein, a two-photon fluorescence probe was discovered. Through sequential ICT processes, it allows successful in vivo visualization of DNA damage in cancer cells by one/two-photon microscopic imaging or by the unaided eye and a hand-held ultraviolet lamp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 26 publications
1
31
0
4
Order By: Relevance
“…A two-photon fluorescent probe 26 has been reported that has the potential to act as a visual tool in the real-time dynamic imaging of DNA damage. 32 The probe operates through sequential intramolecular charge transfer (ICT) processes and allows in vivo visualisation of DNA damage in cancer cells either by one/two photon microscopic imaging or using a hand-held UV lamp.…”
Section: O Oh O Homentioning
confidence: 99%
“…A two-photon fluorescent probe 26 has been reported that has the potential to act as a visual tool in the real-time dynamic imaging of DNA damage. 32 The probe operates through sequential intramolecular charge transfer (ICT) processes and allows in vivo visualisation of DNA damage in cancer cells either by one/two photon microscopic imaging or using a hand-held UV lamp.…”
Section: O Oh O Homentioning
confidence: 99%
“…Ratiometric fluorescent probes are considered as powerful methods for the detection of various analytes in that, through the self-calibration of two emission bands, they eliminate most or all of the ambiguities. [22][23][24][25][26] However, as far as we know, the majority of ratiometric fluorescent probes that are based on an intramolecular charge transfer (ICT) mechanism have short emission shifts (usually <90 nm), [27][28][29] which are vulnerable to the cross-talk of these two emission bands. 30 Therefore, developing ICT-based probes with well-resolved emission peaks, which can precisely image with high resolution, 31 is of importance.…”
Section: Introductionmentioning
confidence: 99%
“…Pra cada complexo, a configuração após 2.25x10 8 passos de MC foi utilizada como condição inicial para DM considerando as geometrias flexíveis no programa Gromacs [164,165]. Para avaliar os efeitos do ânion ao redor do cátion, 4.5x10 8…”
Section: Detalhes Computacionaisunclassified
“…(b) Microfabricação do Cristo Redentor em material polimérico [24]. (c) Resolução da fluorescência promovida pelos processos de absorção de um e de dois fótons Atualmente, com a disponibilidade de lasers de maior intensidade e pulsos de menor duração temporal é possível evitar efeitos térmicos e desenvolver tecnologias que exploram tal processo óptico não linear em diversas áreas do conhecimento, tais como: armazenamento de dados em estruturas tridimensionais [4][5][6], microscopia por fluorescência e imagiamento in vivo [7][8][9], microfabricação [10], terapia fotodinâmica [11,12], limitação óptica [13] e conversão de luz laser (up-conversion) [14]. Um aspecto preliminar e muito importante para o contínuo desenvolvimento de aplicações tecnológicas é a caracterização das propriedades ONL de novos compostos, buscando compreender os mecanismos envolvidos nesses processos e desenvolvendo compostos com maior taxa de A2F [15][16][17].…”
Section: Introductionunclassified
See 1 more Smart Citation